Gambaran Mekanisme Koping pada Lansia di Kota Banda Aceh - Nandini, Nahya; Khairani; Nurhasanah (Jurnal Kesehatan Cendikia Jenius, 2024)
The elderly experience a decline in body functions both physiologically and psychologically. These setbacks can trigger stress that has a negative impact if not immediately resolved. Strengthening coping mechanisms is crucial in managing stress. The purpose of this study is to determine the description of coping mechanisms in the elderly in Banda Aceh City. This study utilizes a descriptive design with a cross-sectional study approach. The study population consists of the elderly residing in the work area of the Kuta Alam Community Health Center in Banda Aceh, totaling 1,747 individuals. Sampling is done using accidental sampling technique, with a minimum sample size of 183 individuals. Data analysis used is frequency distribution. The instrument used is the Brief Cope questionnaire developed by Siaputra, et al. The research results show that coping mechanisms in the elderly are categorized as adaptive, with 173 respondents (94.5%), while there are still 10 individuals with inadequate coping mechanisms. The conclusion is that coping mechanisms in the elderly demonstrate adaptive values. Researchers suggest that the Kuta Alam Community Health Center in Banda Aceh provides education to families to maintain the psychological and physical health of the elderly.